Respon Guru Dan Siswa Terhadap E-Modul Gelombang Bunyi Berbantuan Aplikasi Phyphox Untuk Meningkatkan Kemandirian Dan Hasil Belajar Siswa Kelas XI IPA MAN 2 Lubuklinggau - Wahyu Arini; Ramadhan Fitriyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Abstract: The research of this study was to see the response of teachers and students after participating in learning using the sound wave e-module assisted by the Phyphox application. The research method used is descriptive research type. The subjects of this study were physics teachers and students of class XI IPA MAN 2 Lubuklinggau. The data collection technique was carried out in the form of a response questionnaire. The results of the physics teacher's response analysis obtained 74% with the